Estudo toxicológico pré-clínico de Jatropha gossypiifolia L. - Mariz, Saulo Rios (2007)
The Jatropha gossypiifolia L.(Euphorbiaceae), also known in Brazil as pião-roxo , is a plant with high toxicity. However, some of its therapeutic uses have been proved by experimental studies including a recent paper about the hypotensive effect of this plant. In order to contribute to the development of a herbal drug from this species, this work presents a toxicity assessment in rats with the ethanolic extract (EE) from aerial parts of Jatropha gossypiifolia L. according to Brazilian law (ANVISA-RE 90/2004). In the acute toxicity test we treated Wistar rats (Ratus norvegicus albinus) with the EE in doses of up to 5 g/kg body weight (p.o.). Each group was observed, for 14 days after the treatment, in points such as toxicity signs, lethality, body weight gain and food and water consumption. After this period, the animals which survived were killed for biochemical, hematological and histopathologic analysis. In the chronic toxicity assessment, the rats were handed out on three experimental groups (45 mg/kg, 135 mg/kg and 405 mg/kg). Each group (n=10 per gender and dose) was dosed daily by gavage for a period of 13 weeks. During the treatment, in addition to the parameters cited above, body temperature, tail glucose level and changes in behavior were analyzed (Open field and Rota Rod). At the end of treatment, 40% of animals from each group were killed for the analysis of those parameters already cited in the acute study. The acute treatment shows that only doses equal or higher than 1.8 g/kg body weight (p.o.) cause signals of toxicity as neurological depression and digestive disorders. We observed weight loss and a hind limb paralysis in males (doses 4 and 5 g/kg p.o.). Only in males that survived to higher dose treatment (5 g/kg p.o.) the extract reduced the food intake significantly. This dose also promotes weight loss in females without reduction of food intake. In males treated with 5 g/kg (p.o.), some biochemical, hematological and histopathologic alterations suggest important acute toxicity in the liver, the kidney, the blood and the lung. The LD50 was between 4 and 5 g/kg (p.o.) to males and was higher than 5 g/kg (p.o.) to females. These results indicate that acute toxicity from EE is not significant because the alterations happened just in high doses. However, the neurological depression and digestive disorders were confirmed by chronic evaluation. The lethality among males was 46.6 % (405 mg/kg p.o.), 13,3% (135 mg/kg p.o.) and among females was 13.3 % (doses of 135 mg/kg and 405 mg/kg p.o.). The EE reduces the body weight gain (males 405 mg/kg p.o.). At the colon temperature the extract produces alterations that were not related to the doses in both sexes. In some rats, the product increased glucose level in a reversible way. The locomotion was reduced in females (405 mg/kg p.o.). The increase of total proteins (males 405 mg/kg p.o.) was discrete. It was observed an important increase of glucose level among males (45 mg/Kg p.o.). We also found a discrete anaemia in males (405 mg/kg p.o.) and a increased level of platelet in females of satellite group (135mg/Kg). The histopathologic analysis confirmed the toxicity in liver, kidney and lung. These data show the high chronic toxicity from the product. We propose a chemical refinement on the ethanolic extract to get new fractions with a better risk/benefit relation.